An analysis of English pronunciation learning strategies among Arab EFL learners in Universiti Malaysia Pahang (UMP) - Lardhi, Fatima Ali Salah (2019)
The main aim of this study was to analyse the Pronunciation Learning Strategies (PLS) applied by Arab EFL learners at Universiti Malaysia Pahang (UMP). It also examined the relationship between the use of pronunciation learning strategies and the pronunciation test. Moreover, the study highlighted the factors that led to having mispronunciation in English language. A quantitative research approach was employed using a questionnaire and a pronunciation test. The questionnaire was distributed to 104 Arab EFL learners while the pronunciation test was conducted with 15 Arab EFL learners. The findings of the questionnaire revealed that the participants made a great use of indirect strategy named Metacognitive Strategy. Furthermore, the pronunciation test indicated that Arab EFL learners struggled in pronouncing five English consonant sounds (/p/, /v/, / Ʒ/, /ʧ/ and / ŋ/). As a result, it was reported that there was a positive but weak relationship between the utilization of the PLS and the Arab EFL learners’ scores in the pronunciation test. Besides, the findings from the open-ended questions demonstrated that there were five factors which hindered the learners from having correct English pronunciation namely: lack of formal instruction, lack of practice, learners’ age, lack of exposure and lack of motivation and interest. This study is significant as it has shed some light on the use of PLS to enhance the learners’ abilities to pronounce well. Based on the findings, the study provides pedagogical implications for language instructors and students as well.